Fatigue stipulation of bulk-fill composites: An in vitro appraisal. Issue 9 (September 2015) - Vidhawan, Shruti A.; Yap, Adrian U.; Ornaghi, Barbara P.; Banas, Agnieszka; Banas, Krzysztof; Neo, Jennifer C.; Pfeifer, Carmem S.; Rosa, Vinicius
Abstract Objectives The aim of this study was to determine the Weibull and slow crack growth (SCG) parameters of bulk-fill resin based composites. The strength degradation over time of the materials was also assessed by strength-probability-time (SPT) analysis. Methods Three bulk-fill [Tetric EvoCeram Bulk Fill (TBF); X-tra fil (XTR); Filtek Bulk-fill flowable (BFL)] and a conventional one [Filtek Z250 (Z250)] were studied. Seventy five disk-shaped specimens (12 mm in diameter and 1 mm thick) were prepared by inserting the uncured composites in a stainless steel split mold followed by photoactivation (1200 mW/cm2/20 s) and storage in distilled water (37 °C/24 h). Degree of conversion was evaluated in five specimens by analysis of FT-IR spectra obtained in the mid-IR region. The SCG parameters n (stress corrosion susceptibility coefficient) and σf0 (scaling parameter) were obtained by testing ten specimens in each of the five stress rates: 10−2, 10−1, 100, 101 and 102 MPa/s using a piston-on-three-balls device. Weibull parameter m (Weibull modulus) and σf0 (characteristic strength) were obtained by testing additional 20 specimens at 1 MPa/s. Strength–probability–time (SPT) diagrams were constructed by merging SCG and Weibull parameters. Results BFL and TBF presented higher n values, respectively (40.1 and 25.5). Z250 showed the highest (157.02 MPa) and TBF the lowest (110.90 MPa) σf0 value. Weibull analysis showed m (Weibull modulus) of 9.7, 8.6, 9.7 and 8.9 for TBF, BFL, XTR and Z250, respectively. SPT diagram for 5% probability of failure showed strength decrease of 18% for BFL, 25% for TBF, 32% for XTR and 36% for Z250, respectively, after 5 years as compared to 1 year. Significance The reliability and decadence of strength over time for bulk-fill resin composites studied are, at least, comparable to conventional composites. BFL shows the highest fatigue resistance under all simulations followed by TBF, while XTR was at par with Z250.